Saccade Latency Provides Evidence for Reduced Face Inversion Effects With Higher Autism Traits - Laycock, Robin; Wood, Kylie; Wright, Andrea; Crewther, Sheila G.; Goodale, Melvyn A. (Frontiers in Human Neuroscience, 2020)
Individuals on the autism spectrum are reported to show impairments in processing of social information, including aspects of eye-movements towards faces. Abnormalities in basic-level visual processing are also reported. In the current study, we sought to determine if the latency of saccades made towards social targets (faces) in a natural scene as opposed to inanimate targets (cars) would be related to sub-clinical autism traits in individuals drawn from a neurotypical population. The effect of stimulus inversion was also examined given that difficulties with processing inverted faces is thought to be a function of face expertise. No group differences in saccadic latency was established for face or car targets, regardless of image orientation. However, as expected, we found that individuals with higher autism-like traits did not demonstrate a saccadic face inversion effect, but those with lower autism-like traits did. Neither group showed a car inversion effect. Thus these results suggest that neurotypical individuals with high autism-like traits also show anomalies in detecting and orienting to faces. In particular, the reduced saccadic face inversion effect established in these participants with high autism traits suggests that speed of visual processing and orienting towards faces may be associated with the social difficulties found across the broader autism spectrum.